High-aluminum transparent glass glaze, method for preparing glazed tile using the same, and glazed tile
By designing a high-bar transparent glass glaze formula, the combination of high-aluminum glass powder and low melting point glaze is solved, and the glass glaze surface on the glazed tiles is high hardness, fracture toughness and wear resistance of the glazed tiles surface are achieved, and high transparency and cost-effectiveness are maintained.
Patent Information
- Application Number
- CN202411823289.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The glass glaze on the surface of existing glazed tiles has problems such as low hardness and low fracture toughness, which leads to easy damage and poor wear resistance, which limits its application in the field of building decoration.
High-aluminum transparent glass glaze is used to reasonably design the glaze formula containing high-aluminum glass powder, so that only surface crystallization occurs during the heating process, achieving complete melting within the temperature range of 1160℃-1180℃, and through the liquid phase adhesion and crystal dissolution mechanism of the low-melting point glaze, the tendency of crystallization is reduced and the melting and flattening effect of the glaze is improved.
The high-aluminum transparent glass glaze layer on the surface of the glazed tiles has high hardness, fracture toughness and wear resistance. The micro Vickers hardness can reach up to 6.72GPa, the fracture toughness can reach up to 1.05MPa·m1/2, the wear resistance reaches level 5, and it also has the advantages of high transparency and low cost.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of new glass materials, and in particular to a high-aluminum transparent glass glaze, a method for preparing glazed tiles using the same, and the glazed tiles. Background Art
[0002] In recent years, glazed tiles have become the "new favorite" in the field of ceramic plates, especially ceramic tiles, due to their various patterns, strong three-dimensional patterns, realistic colors, and strong texture, and have broad market prospects. At present, the glass glaze on the surface of glazed tiles on the market generally has the problems of low hardness and low fracture toughness, which makes the glass glaze on the surface of glazed tiles easy to break and poor wear resistance, which greatly limits the application of glazed tiles in the field of architectural decoration. To this end, the applicant proposed a high-aluminum transparent glass glaze with high hardness and strong fracture toughness, a method for preparing glazed tiles using the same, and glazed tiles. Summary of the invention
[0003] In view of the above problems, the present application provides a high-aluminum transparent glass glaze, a method for preparing glazed tiles using the same, and glazed tiles.
[0004] The present invention is achieved through the following technical solutions:
[0005] A high-aluminum transparent glass glaze comprises a low-melting-point glaze and high-aluminum glass powder, wherein the mass ratio of the high-aluminum glass powder to the low-melting-point glaze is (33-42):(58-67); the low-melting-point glaze is prepared from the following raw materials in weight fractions: 3.95-4.32% quartz, 10.05-10.31% sodium fluorosilicate, 10.08-10.58% kaolin, 10.02-10.38% albite, 30.11-30.89% potassium feldspar, 2.02-2.55% wollastonite, 5.02-5.15% talc, 10.18-10.48% dolomite, 8.08-8.68% calcite, 5.87-6.77% barium carbonate and 1.67-2.85% zinc oxide;
[0006] High-aluminum glass powder is prepared from the following oxides in molar percentage: 54.90-60.90% SiO2, 17.60-26.00% Al2O3, 0.00-2.20% MgO, 18.90-20.99% CaO, 0.2% SnO2; the raw material of SiO2 is silicon dioxide with a purity of 99wt%, the raw material of Al2O3 is aluminum oxide with a purity of 99wt%, the raw material of MgO is magnesium oxide with a purity of 98wt%, the raw material of CaO is calcium carbonate with a purity of 99wt%, and the raw material of SnO2 is tin dioxide with a purity of 99wt%.
[0007] Preferably, the preparation method of the low melting point glaze is: after uniformly mixing quartz, sodium fluorosilicate, kaolin, albite, potassium feldspar, wollastonite, talc, dolomite, calcite, barium carbonate and zinc oxide, the mixture is ball-milled and sieved to obtain the low melting point glaze.
[0008] Preferably, the preparation method of high-aluminum glass powder is: silicon dioxide, aluminum oxide, magnesium oxide, calcium carbonate and tin dioxide are mixed uniformly to obtain a batch material, and then the batch material is kept at 1590°C to 1610°C until it is melted and homogenized, and then water quenched to obtain cullet, and the cullet is ball-milled and sieved to obtain high-aluminum glass powder.
[0009] Preferably, the content of SiO2 in the high-aluminum glass powder is 55.00 mol% to 59.15 mol%.
[0010] Preferably, in the high-aluminum glass powder, the content of Al2O3 is 21.30 mol% to 23.80 mol%.
[0011] Preferably, the content of MgO in the high-aluminum glass powder is 1.00 mol% to 1.80 mol%.
[0012] Preferably, in the high-aluminum glass powder, the content of CaO is 19.00 mol% to 20.02 mol%.
[0013] Preferably, the content of SnO2 in the high-aluminum glass powder is 0.20 mol%.
[0014] A method for preparing a glazed tile having a high-aluminum transparent glass glaze layer on the surface by using a high-aluminum transparent glass glaze, comprising the following steps:
[0015] S1: uniformly mixing raw materials having a molar percentage composition corresponding to each oxide of the high-aluminum glass powder to obtain a batch material, melting and homogenizing the batch material and then quenching the batch material to obtain cullet, and then ball-milling the cullet and sieving the cullet to obtain the high-aluminum glass powder;
[0016] S2: uniformly mixing the raw materials corresponding to the weight fraction of each raw material of the low melting point glaze, and then ball milling and sieving to obtain the low melting point glaze;
[0017] S3: uniformly mixing high-aluminum glass powder and low-melting-point glaze in amounts corresponding to the weight fractions of the high-aluminum glass powder and the low-melting-point glaze to obtain a mixed glaze, which is a high-aluminum transparent glass glaze;
[0018] S4: placing the mixed glaze on a fired ceramic substrate, wherein the fired ceramic substrate is a bisque-fired body, and then uniformly heating the ceramic substrate with the mixed glaze from room temperature to a firing temperature, and then keeping the temperature for a period of time, so that the mixed glaze is completely melted and spread on the ceramic substrate to form a uniform glass liquid without bubbles, thereby obtaining a ceramic plate with glass liquid;
[0019] S5: uniformly cooling the ceramic plate with the glass liquid to room temperature to obtain a glazed tile with a glaze layer;
[0020] S6: grinding and polishing the glaze layer surface of the glazed tile with a glaze layer to obtain a glazed tile with a high-aluminum transparent glass glaze layer on the surface.
[0021] Preferably, step S1 specifically includes the following steps: according to the molar percentage composition of each oxide of the high-aluminum glass powder, weigh each raw material, mix them evenly to obtain a batch material, and then keep the batch material at 1590°C to 1610°C until it is melted and homogenized, and then water quench it to obtain cullet, ball-mill the cullet and pass it through a 300-mesh sieve to obtain high-aluminum glass powder.
[0022] Preferably, step S2 specifically includes the following steps: according to the weight fraction of each raw material of the low-melting-point glaze, weigh quartz, sodium fluorosilicate, kaolin, albite, potassium feldspar, wollastonite, talc, dolomite, calcite, barium carbonate and zinc oxide, mix them evenly, perform ball milling, and then pass through a 300-mesh sieve to obtain a low-melting-point glaze.
[0023] Preferably, step S4 specifically includes the following steps: uniformly distributing the mixed glaze obtained in step S3 on a fired ceramic substrate, wherein the fired ceramic substrate is a bisque-fired body, and then, heating the ceramic substrate with the mixed glaze from room temperature to the firing temperature at a rate of 20°C / min, and keeping the temperature for 30-50 minutes to completely melt the mixed glaze and spread it on the ceramic substrate to form a uniform bubble-free glass liquid, thereby obtaining a ceramic plate with glass liquid; in step S4, the firing temperature is 1160-1180°C.
[0024] Preferably, step S5 specifically comprises the following steps: cooling the ceramic plate with the glass liquid to room temperature at a rate of 10° C. / min to obtain a glazed tile with a glaze layer, wherein the glaze layer is located on the upper surface of the glazed tile.
[0025] A glazed tile with a high-aluminum transparent glass glaze layer on the surface is prepared by the method for preparing the glazed tile with a high-aluminum transparent glass glaze layer on the surface using the high-aluminum transparent glass glaze.
[0026] Compared with the prior art, the beneficial technical effects of this application are:
[0027] 1) In the prior art, high-aluminum glass glaze is prepared using high-aluminum glass powder as glaze alone. High-aluminum glass powder has a tendency to crystallize during heating, which is not conducive to the melting of the glaze. Generally, it is difficult to meet the process requirement that the high-aluminum glass powder must be completely melted into glass liquid and flattened at the firing temperature when producing glazed tiles at a temperature below 1200°C. Since the nucleation temperature range of the glass material is usually lower than the crystal growth temperature range, when the overlapping temperature range of the two is small or there is no overlapping temperature range, the tendency of the glass liquid to crystallize during the cooling process is very low. Therefore, the present application reasonably designs a glaze formula containing high-aluminum glass powder, so that the high-aluminum glass powder prepared in step S1 only undergoes surface crystallization (the precipitated crystals are calcium feldspar crystals) during the heating process from room temperature to the firing temperature in step S4, and no body crystallization occurs, and the surface crystallization tendency is low, so that the high-aluminum glass powder can be completely melted within the temperature range of 1160°C-1180°C.
[0028] The selection of high-aluminum glass powder components and the special setting of component dosage in the present application are as follows: Considering that more alkali metal elements are required in low-melting-point glazes to ensure that they can melt at a relatively low temperature, the oxides used to prepare high-aluminum glass powder in the present application do not contain alkali metal oxides, but are replaced by alkaline earth metal oxides, including MgO and CaO, but the total molar content of MgO and CaO does not exceed 25 mol%. Otherwise, the high-aluminum glass has a low viscosity and enhanced ion diffusion at a temperature higher than the glass transition temperature, and is prone to bulk crystallization. In addition, in the present application, SiO2 is a network-forming bulk oxide and is the main component for forming glass. If SiO2 is lower than 54.90 mol%, the glass viscosity is low, and the high-aluminum glass tends to bulk crystallize during the heating process for preparing the high-aluminum glass glaze. If it exceeds 60.90 mol%, the high-aluminum glass will be difficult to melt. Therefore, the molar percentage of SiO2 is selected to be 54.90 mol% to 60.90 mol%. mol% is better; Al2O3 is beneficial to improving the mechanical properties of high-aluminum glass. If Al2O3 is lower than 17.60 mol%, the ratio of the content of modified oxides (i.e., magnesium oxide and calcium oxide) to the content of Al2O3 is high, and the prepared high-aluminum glass glaze contains more Al in a tetracoordinate structure (i.e., AlO4), less Al in a pentacoordinate structure (i.e., AlO5) and Al in a hexacoordinate structure (i.e., AlO6), and the hardness and fracture toughness of the high-aluminum glass glaze will be lower. If Al2O3 exceeds 26.00 mol%, the high-aluminum glass will be difficult to melt during the preparation of the high-aluminum glass glaze. Therefore, the molar percentage of Al2O3 is preferably 17.60 mol% to 26.00 mol%; MgO is used to reduce the melting temperature of high-aluminum glass, but if MgO is higher than 2.20 mol%, high aluminum glass is prone to precipitate cordierite crystals during the heating process of preparing high aluminum glass glaze. The excellent chemical stability of cordierite crystals makes it difficult for them to dissolve in the liquid phase of low melting point glazes. Therefore, the molar percentage of MgO does not exceed 2.20 mol%; CaO can also reduce the melting temperature of high aluminum glass during the preparation of high aluminum glass glaze. If CaO is lower than 18.90 mol%, the fluxing effect is not ideal. However, if CaO is higher than 20.99 mol%, high aluminum glass will precipitate calcium feldspar crystals in addition to aluminum feldspar crystals during the heating process of preparing high aluminum glass glaze. It is difficult for aluminum feldspar crystals to dissolve in the liquid phase of low melting point glazes. Therefore, the molar percentage of CaO is selected to be 18.90-20.99 mol% is better; SnO2 plays a clarifying role as a clarifier in the melting process of high-aluminum glass, which is beneficial to the discharge of bubbles in the glass melt. Usually, the content of the clarifier in the glass batch is very small and will not have a significant effect on the properties and crystallization behavior of the glass. In this high-aluminum glass system, 0.20 mol% SnO2 can achieve a good clarification effect;
[0029] 2) In step S4, since the low-melting-point glaze in the mixed glaze has been completely melted at a relatively low temperature (i.e., less than 1000°C), the liquid phase of the low-melting-point glaze will adhere to the surface of the high-aluminum glass powder in the subsequent process of rising from 1000°C to the firing temperature, which can effectively reduce the number of nucleation activation sites during crystallization on the surface of the high-aluminum glass powder, thereby reducing the tendency of crystallization on the surface of the high-aluminum glass powder, which is conducive to the melting of the high-aluminum glass powder; in addition, the liquid phase of the low-melting-point glaze also provides convenient conditions for the rapid dissolution of crystals on the surface of the high-aluminum glass powder. Specifically, the Al and Si elements (mainly in the form of ions) in the high-viscosity layer formed around the crystals at the initial stage of crystal dissolution can diffuse into the liquid phase of the low-melting-point glaze, reducing the concentration of Al and Si elements around the crystals, thereby accelerating the dissolution process of the crystals, which enables the present application to achieve complete melting of the mixed glaze at a relatively low firing temperature, and spread it on the ceramic substrate to form a uniform bubble-free glass liquid;
[0030] 3) In step S5, the ceramic plate with glass liquid prepared in step S4 of the present application will not undergo crystallization during the process of uniformly cooling down to room temperature in step S5. This is because crystallization includes two processes: nucleation and growth, and the nucleation temperature range is lower than the growth temperature range. In the cooling process from high temperature to low temperature, the crystal nuclei formed only in the low temperature zone cannot grow. Therefore, the transparency of the high-aluminum glass glaze prepared in the present application is effectively guaranteed. At the same time, since the high-aluminum glass glaze prepared in the present application has a high content of aluminum oxide, in addition to the existence of Al in a four-coordinated structure (i.e., AlO4) in the high-aluminum glass glaze, There are Al in a penta-coordinated structure (i.e., AlO5) and Al in a hexa-coordinated structure (i.e., AlO6), and Al in a penta-coordinated structure (i.e., AlO5) and Al in a hexa-coordinated structure (i.e., AlO6) are conducive to the high-aluminum glass glaze to obtain a denser glass network structure. Therefore, the glazed tiles prepared in the present application have high hardness and fracture toughness of the high-aluminum transparent glass glaze on the surface. Through testing, it can be known that the glaze layer of the glazed tiles with a high-aluminum transparent glass glaze layer on the surface prepared by the method described in the present application has a micro-Vickers hardness of up to 6.72 GPa and a fracture toughness of up to 1.05 MPa·m 1 / 2 The visible light transmittance can reach up to 92%, and the wear resistance of the glaze layer of the glazed tile reaches level 5. This shows that the glazed tile with a high-aluminum transparent glass glaze layer on the surface prepared in this application has not only high transparency, but also good hardness, fracture toughness and wear resistance.
[0031] In summary, through the special setting of component selection and component dosage, the high-aluminum glass powder of the present application only undergoes surface crystallization (i.e., the precipitation of calcium feldspar crystals) during the heating process of preparing the high-aluminum glass glaze, which provides favorable conditions for the melting and flattening of the mixed glaze, and no crystallization occurs during the cooling process, so that the prepared high-aluminum glass glaze has both a transparent effect and good hardness and fracture toughness, so that the glass glaze surface of the glazed tile is not easy to break and has good wear resistance; moreover, the high-aluminum transparent glaze of the present application does not use expensive raw materials in the preparation process, so the high-aluminum transparent glaze of the present application also has the advantages of low cost and easy availability of raw materials. DETAILED DESCRIPTION
[0032] Embodiment 1:
[0033] A method for preparing a glazed tile having a high-aluminum transparent glass glaze layer on the surface by using a high-aluminum transparent glass glaze, comprising the following steps:
[0034] S1: According to the molar percentage composition of each oxide of high-aluminum glass powder, as shown in Table 2, 41.91 kg of silicon dioxide, 33.68 kg of aluminum oxide, 24.03 kg of calcium carbonate and 0.38 kg of tin dioxide are weighed respectively, and these raw materials are mixed evenly to obtain a mixture, and then the mixture is placed in a high-temperature ceramic crucible and kept at 1590°C for 10 hours to melt and homogenize, and then water quenched to obtain cullet, and the cullet is ball-milled and sieved through a 300-mesh sieve to obtain high-aluminum glass powder;
[0035] S2: According to the weight fraction composition of each raw material of the low melting point glaze, as shown in Table 3, weigh 3.95Kg of quartz, 10.05Kg of sodium fluorosilicate, 10.08Kg of kaolin, 10.02Kg of albite, 30.11Kg of potassium feldspar, 2.02Kg of wollastonite, 5.15Kg of talc, 10.32Kg of dolomite, 8.68Kg of calcite, 6.77Kg of barium carbonate and 2.85Kg of zinc oxide, mix these raw materials evenly, ball mill them, and then pass through a 300-mesh sieve to obtain a low melting point glaze; the compositions of the raw materials of quartz, sodium fluorosilicate, kaolin, albite, potassium feldspar, wollastonite, talc, dolomite, calcite, barium carbonate and zinc oxide in this application are as shown in Table 1;
[0036] S3: mixing the high-aluminum glass powder obtained in step S1 and the low-melting-point glaze obtained in step 2 in a mass ratio of 33:67 to obtain a mixed glaze, which is a high-aluminum transparent glass glaze;
[0037] S4: evenly distributing the mixed glaze on the fired ceramic substrate, wherein the fired ceramic substrate is a bisque-fired body, and then placing the ceramic substrate with the mixed glaze in a ceramic kiln, heating the temperature from room temperature to a firing temperature of 1160° C. at a rate of 20° C. / min, and then keeping the temperature for 30 minutes, so that the mixed glaze is completely melted and spread on the ceramic substrate to form a uniform glass liquid without bubbles, thereby obtaining a ceramic plate with glass liquid;
[0038] S5: cooling the ceramic plate with the glass liquid to room temperature at a rate of 10° C. / min to obtain a glazed tile with a glaze layer, wherein the glaze layer is located on the surface of the glazed tile;
[0039] S6: Grinding and polishing the glaze layer surface of the glazed tile with a glaze layer to obtain a glazed tile with a high-aluminum transparent glass glaze layer on the surface; wherein the thickness of the high-aluminum transparent glass glaze layer is 1.5 mm.
[0040] The present application takes 10g of the low-melting-point glaze prepared in Example 1 and 10g of the cullet prepared in Example 1 (the particle size of the cullet is between 2mm and 5mm) and places them on a fired ceramic substrate, which is a bisque-fired body. Then, they are placed in a muffle furnace, heated from room temperature to 1000°C at a rate of 20°C / min, and then cooled to room temperature in air. It is found that the low-melting-point glaze has been completely melted into glass liquid, and surface crystallization has occurred in the cullet. Then, the present application performs an X-ray diffraction test on the surface of the cullet and finds that the physical phase on the surface of the cullet is calcium feldspar crystals.
[0041] In addition, in order to verify the performance of the glaze layer of the glazed tile with a high-aluminum transparent glass glaze layer on the surface prepared in Example 1 of the present application, the present application specifically tested the glaze layer. The test found that when the glaze layer of the glazed tile with a high-aluminum transparent glass glaze layer on the surface prepared in Example 1 was tested for its micro-Vickers hardness, a force of 9.8 Newtons was used, and the indentation did not expand. The measured micro-Vickers hardness was 6.72 GPa. In addition, it can be seen from the test that the fracture toughness of the glaze layer of the glazed tile prepared in Example 1 is 1.05 MPa·m 1 / 2, as shown in Table 4; in addition, this embodiment also adopts standard GB / T3810.7-2016 to test the wear resistance of the glaze layer of the glazed tile. The test shows that the wear resistance of the glaze layer of the glazed tile prepared in this embodiment reaches level 5. In this embodiment, in addition to the Al tetracoordinate structure (i.e., AlO4) in the glass glaze layer, there may also be Al pentacoordinate structure (i.e., AlO5) and Al hexacoordinate structure (i.e., AlO6), and the Al pentacoordinate structure (i.e., AlO5) and Al hexacoordinate structure (i.e., AlO6) are conducive to making the glaze layer obtain a denser glass network structure, thereby effectively improving the hardness, fracture toughness and wear resistance of the high-aluminum transparent glass glaze layer; in addition, the present application also grinds off the ceramic substrate of the glazed tile prepared in Example 1, and tests the visible light transmittance of the remaining glaze layer. It can be seen that within the visible light range of 500-600nm, the transmittance of the glaze layer with a thickness of 1.5mm is 90%. This is because the glass glaze layer is amorphous, there are no grains, and thus there is no light scattering caused by the grains, so it has high transparency.
[0042] Embodiment 2:
[0043] A method for preparing a glazed tile having a high-aluminum transparent glass glaze layer on the surface by using a high-aluminum transparent glass glaze, comprising the following steps:
[0044] S1: According to the molar percentage composition of each oxide of high-aluminum glass powder, as shown in Table 2, 48.89 kg of silicon dioxide, 23.97 kg of aluminum oxide, 1.20 kg of magnesium oxide, 25.54 kg of calcium carbonate and 0.40 kg of tin dioxide are weighed respectively, and these raw materials are mixed evenly to obtain a mixture, and then the mixture is placed in a high-temperature ceramic crucible and kept at 1610° C. for 13 hours to melt and homogenize, and then water quenched to obtain cullet, and the cullet is ball-milled and sieved through a 300-mesh sieve to obtain high-aluminum glass powder;
[0045] S2: According to the weight fraction composition of each raw material of the low melting point glaze, as shown in Table 3, weigh 4.32Kg of quartz, 10.31Kg of sodium fluorosilicate, 10.56Kg of kaolin, 10.28Kg of albite, 30.82Kg of potassium feldspar, 2.55Kg of wollastonite, 5.02Kg of talc, 10.28Kg of dolomite, 8.12Kg of calcite, 6.07Kg of barium carbonate and 1.67Kg of zinc oxide, mix these raw materials evenly, ball mill them, and then pass through a 300-mesh sieve to obtain a low melting point glaze; the compositions of the raw materials of quartz, sodium fluorosilicate, kaolin, albite, potassium feldspar, wollastonite, talc, dolomite, calcite, barium carbonate and zinc oxide in this application are as shown in Table 1;
[0046] S3: uniformly mixing the high-aluminum glass powder obtained in step S1 and the low-melting-point glaze obtained in step 2 in a mass ratio of 40:60 to obtain a mixed glaze, which is a high-aluminum transparent glass glaze;
[0047] S4: evenly distributing the mixed glaze on the fired ceramic substrate, which is a bisque-fired body, and then placing the ceramic substrate with the mixed glaze in a ceramic kiln, heating the temperature from room temperature to a firing temperature of 1180°C at a rate of 20°C / min, and then keeping the temperature for 50 minutes, so that the mixed glaze is completely melted and spread on the ceramic substrate to form a uniform glass liquid without bubbles, thereby obtaining a ceramic plate with glass liquid;
[0048] S5: cooling the ceramic plate with the glass liquid to room temperature at a rate of 10° C. / min to obtain a glazed tile with a glaze layer, wherein the glaze layer is located on the surface of the glazed tile;
[0049] S6: Grinding and polishing the glaze layer surface of the glazed tile with a glaze layer to obtain a glazed tile with a high-aluminum transparent glass glaze layer on the surface; wherein the thickness of the high-aluminum transparent glass glaze layer is 1.5 mm.
[0050] The present application takes 10g of the low-melting-point glaze prepared in Example 2 and 10g of the cullet prepared in Example 2 (the particle size of the cullet is between 2mm and 5mm) and places them on the fired ceramic substrate, which is a bisque-fired body. Then, they are placed in a muffle furnace, heated from room temperature to 1000°C at a rate of 20°C / min, and then cooled to room temperature in air. It is found that the low-melting-point glaze has been completely melted into glass liquid, and the cullet has undergone surface crystallization. Then, the present application performs an X-ray diffraction test on the surface of the cullet and finds that the physical phase on the surface of the cullet is calcium feldspar crystals.
[0051] In addition, in order to verify the performance of the glaze layer of the glazed tile with a high-aluminum transparent glass glaze layer on the surface prepared in Example 2 of the present application, the present application specifically tested the glaze layer. The test found that when the glaze layer of the glazed tile with a high-aluminum transparent glass glaze layer on the surface prepared in Example 2 was tested for its micro-Vickers hardness, a force of 9.8 Newtons was used, and the indentation did not expand. The measured micro-Vickers hardness was 6.50 GPa. In addition, it can be seen from the test that the fracture toughness of the glaze layer of the glazed tile prepared in Example 2 is 0.95 MPa·m 1 / 2, as shown in Table 4; in addition, this embodiment also adopts standard GB / T3810.7-2016 to test the wear resistance of the glaze layer of the glazed tile. The test shows that the wear resistance of the glaze layer of the glazed tile prepared in this embodiment reaches level 5. In this embodiment, in addition to the Al tetracoordinate structure (i.e., AlO4) in the glass glaze layer, there may also be Al pentacoordinate structure (i.e., AlO5) and Al hexacoordinate structure (i.e., AlO6), and the Al pentacoordinate structure (i.e., AlO5) and Al hexacoordinate structure (i.e., AlO6) are conducive to making the glaze layer obtain a denser glass network structure, thereby effectively improving the hardness, fracture toughness and wear resistance of the high-aluminum transparent glass glaze layer; in addition, the present application also grinds off the ceramic substrate of the glazed tiles prepared in Example 2, and tests the visible light transmittance of the remaining glaze layer. It can be seen that within the visible light range of 500-600nm, the transmittance of the glaze layer with a thickness of 1.5mm is 91%. This is because the glass glaze layer is amorphous, there are no grains, and thus there is no light scattering caused by the grains, and therefore, it has high transparency.
[0052] Embodiment three:
[0053] A method for preparing a glazed tile having a high-aluminum transparent glass glaze layer on the surface by using a high-aluminum transparent glass glaze, comprising the following steps:
[0054] S1: According to the molar percentage composition of each oxide of high-aluminum glass powder, as shown in Table 2, 46.29 kg of silicon dioxide, 24.58 kg of aluminum oxide, 1.07 kg of magnesium oxide, 27.66 kg of calcium carbonate and 0.40 kg of tin dioxide are weighed respectively, and these raw materials are mixed evenly to obtain a mixture, and then the mixture is placed in a high-temperature ceramic crucible and kept at 1600° C. for 12 hours to melt and homogenize, and then water quenched to obtain cullet, and the cullet is ball-milled and sieved through a 300-mesh sieve to obtain high-aluminum glass powder;
[0055] S2: According to the weight fraction composition of each raw material of the low melting point glaze, as shown in Table 3, weigh quartz 4.01Kg, sodium fluorosilicate 10.28Kg, kaolin 10.28Kg, albite 10.28Kg, potassium feldspar 30.82Kg, wollastonite 2.32Kg, talc 5.12Kg, dolomite 10.39Kg, calcite 8.33Kg, barium carbonate 6.27Kg and zinc oxide 1.90Kg, mix these raw materials evenly and then ball mill them, and then pass through a 300 mesh sieve to obtain a low melting point glaze, which is a high aluminum transparent glass glaze; the components of the raw materials of quartz, sodium fluorosilicate, kaolin, albite, potassium feldspar, wollastonite, talc, dolomite, calcite, barium carbonate and zinc oxide in this application are as shown in Table 1;
[0056] S3: uniformly mixing the high-aluminum glass powder obtained in step S1 and the low-melting-point glaze obtained in step 2 in a mass ratio of 42:58 to obtain a mixed glaze, which is a high-aluminum transparent glass glaze;
[0057] S4: evenly distributing the mixed glaze obtained in step S3 on the fired ceramic substrate, which is a bisque-fired body, and then placing the ceramic substrate with the mixed glaze in a ceramic kiln, heating the temperature from room temperature to a firing temperature of 1170°C at a rate of 20°C / min, and then keeping the temperature for 50 minutes, so that the mixed glaze is completely melted and spread on the ceramic substrate to form a uniform glass liquid without bubbles, thereby obtaining a ceramic plate with glass liquid;
[0058] S5: cooling the ceramic plate with the glass liquid to room temperature at a rate of 10° C. / min to obtain a glazed tile with a glaze layer, wherein the glaze layer is located on the surface of the glazed tile;
[0059] S6: Grinding and polishing the glaze layer surface of the glazed tile with a glaze layer to obtain a glazed tile with a high-aluminum transparent glass glaze layer on the surface; wherein the thickness of the high-aluminum transparent glass glaze layer is 1.5 mm.
[0060] The present application takes 10g of the low-melting-point glaze prepared in Example 3 and 10g of the cullet prepared in Example 3 (the particle size of the cullet is between 2mm and 5mm) and places them on the fired ceramic substrate, which is a bisque-fired body. Then, they are placed in a muffle furnace, heated from room temperature to 1000°C at a rate of 20°C / min, and then cooled to room temperature in air. It is found that the low-melting-point glaze has been completely melted into glass liquid, and the cullet has undergone surface crystallization. Then, the present application performs an X-ray diffraction test on the surface of the cullet and finds that the physical phase on the surface of the cullet is calcium feldspar crystals.
[0061] In addition, in order to verify the performance of the glaze layer of the glazed tile with a high-aluminum transparent glass glaze layer on the surface prepared in Example 3 of the present application, the present application specifically tested the glaze layer. The test found that when the glaze layer of the glazed tile with a high-aluminum transparent glass glaze layer on the surface prepared in Example 3 was tested for its micro-Vickers hardness, a force of 9.8 Newtons was used, and the indentation did not expand. The measured micro-Vickers hardness was 6.66 GPa. In addition, it can be seen from the test that the fracture toughness of the glaze layer of the glazed tile prepared in Example 3 is 0.99 MPa·m 1 / 2, as shown in Table 4; in addition, this embodiment also adopts standard GB / T3810.7-2016 to test the wear resistance of the glaze layer of the glazed tile. The test shows that the wear resistance of the glaze layer of the glazed tile prepared in this embodiment reaches level 5. In this embodiment, in addition to the Al tetracoordinate structure (i.e., AlO4) in the glass glaze layer, there may also be Al pentacoordinate structure (i.e., AlO5) and Al hexacoordinate structure (i.e., AlO6), and the Al pentacoordinate structure (i.e., AlO5) and Al hexacoordinate structure (i.e., AlO6) are conducive to making the glaze layer obtain a denser glass network structure, thereby effectively improving the hardness, fracture toughness and wear resistance of the high-aluminum transparent glass glaze layer; in addition, the present application also grinds off the ceramic substrate of the glazed tiles prepared in Example 3, and tests the visible light transmittance of the remaining glaze layer. It can be seen that within the visible light range of 500-600nm, the transmittance of the glaze layer with a thickness of 1.5mm is 90%. This is because the glass glaze layer is amorphous, there are no grains, and thus there is no light scattering caused by the grains, so it has high transparency.
[0062] Embodiment 4:
[0063] A method for preparing a glazed tile having a high-aluminum transparent glass glaze layer on the surface by using a high-aluminum transparent glass glaze, comprising the following steps:
[0064] S1: According to the molar percentage composition of each oxide of high-aluminum glass powder, as shown in Table 2, 42.97 kg of silicon dioxide, 29.65 kg of aluminum oxide, 0.95 kg of magnesium oxide, 26.04 kg of calcium carbonate and 0.39 kg of tin dioxide are weighed respectively, and these raw materials are mixed evenly to obtain a mixture, and then the mixture is placed in a high-temperature ceramic crucible and kept at 1590° C. for 12 hours to melt and homogenize, and then water quenched to obtain cullet, and the cullet is ball-milled and sieved through a 300-mesh sieve to obtain high-aluminum glass powder;
[0065] S2: According to the weight fraction composition of each raw material of the low melting point glaze, as shown in Table 3, weigh quartz 4.11Kg, sodium fluorosilicate 10.23Kg, kaolin 10.28Kg, albite 10.28Kg, potassium feldspar 30.82Kg, wollastonite 2.33Kg, talc 5.14Kg, dolomite 10.18Kg, calcite 8.26Kg, barium carbonate 6.52Kg and zinc oxide 1.85Kg, mix these raw materials evenly, ball mill them, and then pass through a 300 mesh sieve to obtain a low melting point glaze; the components of the raw materials of quartz, sodium fluorosilicate, kaolin, albite, potassium feldspar, wollastonite, talc, dolomite, calcite, barium carbonate and zinc oxide in this application are as shown in Table 1;
[0066] S3: mixing the high-aluminum glass powder obtained in step S1 and the low-melting-point glaze obtained in step 2 in a ratio of 38:62 to obtain a mixed glaze, which is a high-aluminum transparent glass glaze;
[0067] S4: evenly distributing the mixed glaze obtained in step S3 on the fired ceramic substrate, which is a bisque-fired body, and then placing the ceramic substrate with the mixed glaze in a ceramic kiln, heating the temperature from room temperature to a firing temperature of 1165°C at a rate of 20°C / min, and then keeping the temperature for 40 minutes, so that the mixed glaze is completely melted and spread on the ceramic substrate to form a uniform glass liquid without bubbles, thereby obtaining a ceramic plate with glass liquid;
[0068] S5: cooling the ceramic plate with the glass liquid to room temperature at a rate of 10° C. / min to obtain a glazed tile with a glaze layer, wherein the glaze layer is located on the surface of the glazed tile;
[0069] S6: Grinding and polishing the glaze layer surface of the glazed tile with a glaze layer to obtain a glazed tile with a high-aluminum transparent glass glaze layer on the surface; wherein the thickness of the high-aluminum transparent glass glaze layer is 1.5 mm.
[0070] The present application takes 10g of the low-melting-point glaze prepared in Example 4 and 10g of the cullet prepared in Example 4 (the particle size of the cullet is between 2mm and 5mm) and places them on the fired ceramic substrate, which is a bisque-fired body. Then, they are placed in a muffle furnace, heated from room temperature to 1000°C at a rate of 20°C / min, and then cooled to room temperature in air. It is found that the low-melting-point glaze has been completely melted into glass liquid, and the cullet has undergone surface crystallization. Then, the present application performs an X-ray diffraction test on the surface of the cullet and finds that the physical phase on the surface of the cullet is calcium feldspar crystals.
[0071] In addition, in order to verify the performance of the glaze layer of the glazed tile with a high-aluminum transparent glass glaze layer on the surface prepared in Example 4 of the present application, the present application specifically tested the glaze layer. The test found that when the glaze layer of the glazed tile with a high-aluminum transparent glass glaze layer on the surface prepared in Example 4 was tested for its micro-Vickers hardness, a force of 9.8 Newtons was used, and the indentation did not expand. The measured micro-Vickers hardness was 6.57 GPa. In addition, it can be seen from the test that the fracture toughness of the glaze layer of the glazed tile prepared in Example 4 is 0.91 MPa·m 1 / 2, as shown in Table 4; in addition, this embodiment also adopts standard GB / T3810.7-2016 to test the wear resistance of the glaze layer of the glazed tile. The test shows that the wear resistance of the glaze layer of the glazed tile prepared in this embodiment reaches level 5. In this embodiment, in addition to the Al tetracoordinate structure (i.e., AlO4) in the glass glaze layer, there may also be Al pentacoordinate structure (i.e., AlO5) and Al hexacoordinate structure (i.e., AlO6), and the Al pentacoordinate structure (i.e., AlO5) and Al hexacoordinate structure (i.e., AlO6) are conducive to making the glaze layer obtain a denser glass network structure, thereby effectively improving the hardness, fracture toughness and wear resistance of the high-aluminum transparent glass glaze layer; in addition, the present application also grinds off the ceramic substrate of the glazed tiles prepared in Example 4, and tests the visible light transmittance of the remaining glaze layer. It can be seen that within the visible light range of 500-600nm, the transmittance of the glaze layer with a thickness of 1.5mm is 90%. This is because the glass glaze layer is amorphous, there are no grains, and thus there is no light scattering due to the grains, so it has high transparency.
[0072] Embodiment five:
[0073] A method for preparing a glazed tile having a high-aluminum transparent glass glaze layer on the surface by using a high-aluminum transparent glass glaze, comprising the following steps:
[0074] S1: According to the molar percentage composition of each oxide of high-aluminum glass powder, as shown in Table 2, 46.79 kg of silicon dioxide, 25.71 kg of aluminum oxide, 0.53 kg of magnesium oxide, 26.57 kg of calcium carbonate and 0.40 kg of tin dioxide are weighed respectively, and these raw materials are mixed evenly to obtain a mixture, and then the mixture is placed in a high-temperature ceramic crucible and kept at 1605°C for 10 hours to melt and homogenize, and then water quenched to obtain cullet, and the cullet is ball-milled and sieved through a 300-mesh sieve to obtain high-aluminum glass powder;
[0075] S2: According to the weight fraction composition of each raw material of the low melting point glaze, as shown in Table 3, weigh 4.26Kg of quartz, 10.28Kg of sodium fluorosilicate, 10.58Kg of kaolin, 10.38Kg of albite, 30.89Kg of potassium feldspar, 2.45Kg of wollastonite, 5.07Kg of talc, 10.31Kg of dolomite, 8.08Kg of calcite, 5.87Kg of barium carbonate and 1.83Kg of zinc oxide, mix these raw materials evenly, ball mill them, and then pass through a 300-mesh sieve to obtain a low melting point glaze; the compositions of the raw materials of quartz, sodium fluorosilicate, kaolin, albite, potassium feldspar, wollastonite, talc, dolomite, calcite, barium carbonate and zinc oxide in this application are as shown in Table 1;
[0076] S3: mixing the high-aluminum glass powder obtained in step S1 and the low-melting-point glaze obtained in step 2 in a ratio of 38:62 to obtain a mixed glaze, which is a high-aluminum transparent glass glaze;
[0077] S4: evenly distributing the mixed glaze obtained in step S3 on the fired ceramic substrate, which is a bisque-fired body, and then placing the ceramic substrate with the mixed glaze in a ceramic kiln, heating the temperature from room temperature to a firing temperature of 1175°C at a rate of 20°C / min, and then keeping the temperature for 50 minutes, so that the mixed glaze is completely melted and spread on the ceramic substrate to form a uniform glass liquid without bubbles, thereby obtaining a ceramic plate with glass liquid;
[0078] S5: cooling the ceramic plate with the glass liquid to room temperature at a rate of 10° C. / min to obtain a glazed tile with a glaze layer, wherein the glaze layer is located on the surface of the glazed tile;
[0079] S6: Grinding and polishing the glaze layer surface of the glazed tile with a glaze layer to obtain a glazed tile with a high-aluminum transparent glass glaze layer on the surface; wherein the thickness of the high-aluminum transparent glass glaze layer is 1.5 mm.
[0080] The present application takes 10g of the low-melting-point glaze prepared in Example 5 and 10g of the cullet prepared in Example 5 (the particle size of the cullet is between 2mm and 5mm) and places them on the fired ceramic substrate, which is a bisque-fired body. Then, they are placed in a muffle furnace, heated from room temperature to 1000°C at a rate of 20°C / min, and then cooled to room temperature in air. It is found that the low-melting-point glaze has been completely melted into glass liquid, and the cullet has undergone surface crystallization. Then, the present application performs an X-ray diffraction test on the surface of the cullet and finds that the physical phase on the surface of the cullet is calcium feldspar crystals.
[0081] In addition, in order to verify the performance of the glaze layer of the glazed tile with a high-aluminum transparent glass glaze layer on the surface prepared in Example 5 of the present application, the present application specifically tested the glaze layer. The test found that when the glaze layer of the glazed tile with a high-aluminum transparent glass glaze layer on the surface prepared in Example 5 was tested for its micro-Vickers hardness, a force of 9.8 Newtons was used, and the indentation did not expand. The measured micro-Vickers hardness was 6.55 GPa. In addition, it can be seen from the test that the fracture toughness of the glaze layer of the glazed tile prepared in Example 5 is 0.90 MPa·m 1 / 2, as shown in Table 4; in addition, this embodiment also adopts standard GB / T3810.7-2016 to test the wear resistance of the glaze layer of the glazed tile. The test shows that the wear resistance of the glaze layer of the glazed tile prepared in this embodiment reaches level 5. In this embodiment, in addition to the Al tetracoordinate structure (i.e., AlO4) in the glass glaze layer, there may also be Al pentacoordinate structure (i.e., AlO5) and Al hexacoordinate structure (i.e., AlO6), and the Al pentacoordinate structure (i.e., AlO5) and Al hexacoordinate structure (i.e., AlO6) are conducive to making the glaze layer obtain a denser glass network structure, thereby effectively improving the hardness, fracture toughness and wear resistance of the high-aluminum transparent glass glaze layer; in addition, the present application also grinds off the ceramic substrate of the glazed tiles prepared in Example 5, and tests the visible light transmittance of the remaining glaze layer. It can be seen that within the visible light range of 500-600nm, the transmittance of the glaze layer with a thickness of 1.5mm is 92%. This is because the high-aluminum transparent glass glaze layer is amorphous, there are no grains, and thus there is no light scattering due to the grains, so it has high transparency.
[0082] Embodiment 6
[0083] A method for preparing a glazed tile having a high-aluminum transparent glass glaze layer on the surface by using a high-aluminum transparent glass glaze, comprising the following steps:
[0084] S1: According to the molar percentage composition of each oxide of high-aluminum glass powder, as shown in Table 2, 44.68 kg of silicon dioxide, 28.01 kg of aluminum oxide, 1.12 kg of magnesium oxide, 25.81 kg of calcium carbonate and 0.39 kg of tin dioxide are weighed respectively, and these raw materials are mixed evenly to obtain a mixture, and then the mixture is placed in a high-temperature ceramic crucible and kept at 1590° C. for 11 hours to melt and homogenize, and then water quenched to obtain cullet, and the cullet is ball-milled and sieved through a 300-mesh sieve to obtain high-aluminum glass powder;
[0085] S2: According to the weight fraction composition of each raw material of the low melting point glaze, as shown in Table 3, weigh 4.11Kg of quartz, 10.22Kg of sodium fluorosilicate, 10.28Kg of kaolin, 10.28Kg of albite, 30.82Kg of potassium feldspar, 2.35Kg of wollastonite, 5.13Kg of talc, 10.48Kg of dolomite, 8.27Kg of calcite, 6.21Kg of barium carbonate and 1.85Kg of zinc oxide, mix these raw materials evenly, ball mill them, and then pass through a 300-mesh sieve to obtain a low melting point glaze; the compositions of the raw materials of quartz, sodium fluorosilicate, kaolin, albite, potassium feldspar, wollastonite, talc, dolomite, calcite, barium carbonate and zinc oxide in this application are as shown in Table 1;
[0086] S3: mixing the high-aluminum glass powder obtained in step S1 and the low-melting-point glaze obtained in step 2 in a ratio of 38:62 to obtain a mixed glaze, which is a high-aluminum transparent glass glaze;
[0087] S4: evenly distributing the mixed glaze obtained in step S3 on the fired ceramic substrate, which is a bisque-fired body, and then placing the ceramic substrate with the mixed glaze in a ceramic kiln, heating the temperature from room temperature to a firing temperature of 1165°C at a rate of 20°C / min, and then keeping the temperature for 50 minutes, so that the mixed glaze is completely melted and spread on the ceramic substrate to form a uniform glass liquid without bubbles, thereby obtaining a ceramic plate with glass liquid;
[0088] S5: cooling the ceramic plate with the glass liquid to room temperature at a rate of 10° C. / min to obtain a glazed tile with a glaze layer, wherein the glaze layer is located on the surface of the glazed tile;
[0089] S6: Grinding and polishing the glaze layer surface of the glazed tile with a glaze layer to obtain a glazed tile with a high-aluminum transparent glass glaze layer on the surface; wherein the thickness of the high-aluminum transparent glass glaze layer is 1.5 mm.
[0090] The present application takes 10g of the low-melting-point glaze prepared in Example 6 and 10g of the cullet prepared in Example 6 (the particle size of the cullet is between 2mm and 5mm) and places them on the fired ceramic substrate, which is a bisque-fired body. Then, they are placed in a muffle furnace, heated from room temperature to 1000°C at a rate of 20°C / min, and then cooled to room temperature in air. It is found that the low-melting-point glaze has been completely melted into glass liquid, and the cullet has undergone surface crystallization. Then, the present application performs an X-ray diffraction test on the surface of the cullet and finds that the physical phase on the surface of the cullet is calcium feldspar crystals.
[0091] In addition, in order to verify the performance of the glaze layer of the glazed tile with a high-aluminum transparent glass glaze layer on the surface prepared in Example 6 of the present application, the present application specifically tested the glaze layer. The test found that when the glaze layer of the glazed tile with a high-aluminum transparent glass glaze layer on the surface prepared in Example 6 was tested for its micro-Vickers hardness, a force of 9.8 Newtons was used, and the indentation did not expand. The measured micro-Vickers hardness was 6.60 GPa. In addition, it can be seen from the test that the fracture toughness of the glaze layer of the glazed tile prepared in Example 6 is 1.02 MPa·m 1 / 2, as shown in Table 4; in addition, this embodiment also adopts standard GB / T3810.7-2016 to test the wear resistance of the glaze layer of the glazed tile. The test shows that the wear resistance of the glaze layer of the glazed tile prepared in this embodiment reaches level 5. In this embodiment, in addition to the Al tetracoordinate structure (i.e., AlO4) in the glass glaze layer, there may also be Al pentacoordinate structure (i.e., AlO5) and Al hexacoordinate structure (i.e., AlO6), and the Al pentacoordinate structure (i.e., AlO5) and Al hexacoordinate structure (i.e., AlO6) are conducive to making the glaze layer obtain a denser glass network structure, thereby effectively improving the hardness, fracture toughness and wear resistance of the high-aluminum transparent glass glaze layer; in addition, the present application also grinds off the ceramic substrate of the glazed tiles prepared in Example 6, and tests the visible light transmittance of the remaining glaze layer. It can be seen that within the visible light range of 500-600nm, the transmittance of the glaze layer with a thickness of 1.5mm is 91%. This is because the glass glaze layer is amorphous, there are no grains, and thus there is no light scattering caused by the grains, so it has high transparency.
[0092] Table 1 Composition of raw materials in low melting point glaze (wt%)
[0093]
[0094] Table 2 Amounts of components used in preparing high-aluminum glass powder in the examples
[0095]
[0096] Table 3 Amounts of various raw materials used in preparing low melting point glazes in the examples
[0097]
[0098] Table 4 Physical properties of the glaze layer of the glazed tiles prepared in each embodiment
[0099]
[0100] The above is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A high-aluminum transparent glass glaze, characterized in that: It includes low melting point glaze and high aluminum glass powder, and the mass ratio of the high aluminum glass powder to the low melting point glaze is (33-42):(58-67); The low melting point glaze is prepared from the following raw materials in weight fractions: 3.95-4.32% quartz, 10.05-10.31% sodium fluorosilicate, 10.08-10.58% kaolin, 10.02-10.38% albite, 30.11-30.89% potassium feldspar, 2.02-2.55% wollastonite, 5.02-5.15% talc, 10.18-10.48% dolomite, 8.08-8.68% calcite, 5.87-6.77% barium carbonate and 1.67-2.85% zinc oxide; High-aluminum glass powder is prepared from the following oxides in molar percentage: 54.90-60.90% SiO2, 17.60-26.00% Al2O3, 0.00-2.20% MgO, 18.90-20.99% CaO, 0.2% SnO2; the raw material of SiO2 is silicon dioxide with a purity of 99wt%, the raw material of Al2O3 is aluminum oxide with a purity of 99wt%, the raw material of MgO is magnesium oxide with a purity of 98wt%, the raw material of CaO is calcium carbonate with a purity of 99wt%, and the raw material of SnO2 is tin dioxide with a purity of 99wt%.
2. The high-aluminum transparent glass enamel according to claim 1, characterized in that: The preparation method of the low melting point glaze is as follows: after uniformly mixing quartz, sodium fluorosilicate, kaolin, albite, potassium feldspar, wollastonite, talc, dolomite, calcite, barium carbonate and zinc oxide, the mixture is ball-milled and sieved to obtain the low melting point glaze.
3. A high-aluminum transparent glass enamel according to claim 1 or 2, characterized in that: The preparation method of high-aluminum glass powder is as follows: silicon dioxide, aluminum oxide, magnesium oxide, calcium carbonate and tin dioxide are uniformly mixed to obtain a batch material, and then the batch material is kept at 1590°C to 1610°C until it is melted and homogenized, and then water quenched to obtain cullet, and the cullet is ball-milled and sieved to obtain high-aluminum glass powder.
4. A method for preparing a glazed tile having a high-aluminum transparent glass glaze layer on the surface by using a high-aluminum transparent glass glaze, characterized in that: The high-aluminum transparent glass glaze is the high-aluminum transparent glass glaze according to claim 1, and the method for preparing a glazed tile having a high-aluminum transparent glass glaze layer on the surface by using the high-aluminum transparent glass glaze comprises the following steps: S1: uniformly mixing raw materials having a molar percentage composition corresponding to each oxide of the high-aluminum glass powder to obtain a batch material, melting and homogenizing the batch material and then quenching the batch material to obtain cullet, and then ball-milling the cullet and sieving the cullet to obtain the high-aluminum glass powder; S2: uniformly mixing the raw materials corresponding to the weight fraction of each raw material of the low melting point glaze, and then ball milling and sieving to obtain the low melting point glaze; S3: uniformly mixing high-aluminum glass powder and low-melting-point glaze in amounts corresponding to the weight fractions of the high-aluminum glass powder and the low-melting-point glaze to obtain a mixed glaze, which is a high-aluminum transparent glass glaze; S4: placing the mixed glaze on a fired ceramic substrate, wherein the fired ceramic substrate is a bisque-fired body, and then uniformly heating the ceramic substrate with the mixed glaze from room temperature to a firing temperature, and then keeping the temperature for a period of time, so that the mixed glaze is completely melted and spread on the ceramic substrate to form a uniform glass liquid without bubbles, thereby obtaining a ceramic plate with glass liquid; S5: uniformly cooling the ceramic plate with the glass liquid to room temperature to obtain a glazed tile with a glaze layer; S6: grinding and polishing the glaze layer surface of the glazed tile with a glaze layer to obtain a glazed tile with a high-aluminum transparent glass glaze layer on the surface.
5. The method for preparing glazed tiles with a high-aluminum transparent glass glaze layer on the surface by using high-aluminum transparent glass glaze according to claim 4, characterized in that: Step S1 specifically includes the following steps: according to the molar percentage composition of each oxide of the high-aluminum glass powder, weigh each raw material, mix them evenly to obtain a batch material, and then keep the batch material at 1590°C to 1610°C until it is melted and homogenized, and then water quench it to obtain cullet, ball-mill the cullet and pass it through a 300-mesh sieve to obtain high-aluminum glass powder.
6. The method for preparing glazed tiles with a high-aluminum transparent glass glaze layer on the surface by using high-aluminum transparent glass glaze according to claim 4, characterized in that: Step S2 specifically includes the following steps: according to the weight fraction of each raw material of the low-melting-point glaze, weigh quartz, sodium fluorosilicate, kaolin, albite, potassium feldspar, wollastonite, talc, dolomite, calcite, barium carbonate and zinc oxide, mix them evenly, perform ball milling, and then pass through a 300-mesh sieve to obtain a low-melting-point glaze.
7. The method for preparing glazed tiles with a high-aluminum transparent glass glaze layer on the surface by using high-aluminum transparent glass glaze according to claim 4, characterized in that: Step S4 specifically includes the following steps: evenly distributing the mixed glaze obtained in step S3 on the fired ceramic substrate, wherein the fired ceramic substrate is a bisque-fired body, and then, heating the ceramic substrate with the mixed glaze from room temperature to the firing temperature at a rate of 20°C / min, and keeping the temperature for 30-50 minutes to completely melt the mixed glaze and spread it on the ceramic substrate to form a uniform bubble-free glass liquid, thereby obtaining a ceramic plate with glass liquid; in step S4, the firing temperature is 1160-1180°C.
8. The method for preparing glazed tiles with a high-aluminum transparent glass glaze layer on the surface by using high-aluminum transparent glass glaze according to claim 4, characterized in that: Step S5 specifically includes the following steps: cooling the ceramic plate with the glass liquid to room temperature at a rate of 10° C. / min to obtain a glazed tile with a glaze layer, wherein the glaze layer is located on the surface of the glazed tile.
9. A glazed tile having a high-aluminum transparent glass glaze layer on its surface, wherein the glazed tile having a high-aluminum transparent glass glaze layer on its surface is prepared by the method for preparing a glazed tile having a high-aluminum transparent glass glaze layer on its surface using a high-aluminum transparent glass glaze as described in any one of claims 4 to 8.
Citation Information
Patent Citations
A super-flat glaze frit and a method of manufacturing super spar from the same
CN105541112A
High-wear-resistance polished glaze material and preparation method thereof
CN111333328A